(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article is dedicated to a comprehensive examination of the theoretical foundations of speech etiquette, analysis of its historical formation and cultural development, as well as research on the contribution of Russian scholars to the formation of modern speech behavior theory. Based on the analysis of the scientific works of L. P. Yakubinsky, N. I. Formanovskaya, E. M. Vereshchagin, V. G. Kostomarov, Yu. N. Karaulov, and other researchers, the content of the concepts of "speech etiquette," "communicative norm," "politeness," and "linguistic personality" is revealed. The work presents the main stages of speech etiquette development – from primitive communicative rituals to modern digital forms of communication. Special attention is paid to the national–cultural specifics of Russian speech etiquette, its connection with the traditions and social norms of Russian society.